PARADOKS PENGATURAN HUKUM PROSTITUSI DI INDONESIA - Khoiruddin Manahan Siregar (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2019)
The practice of prostitution is a practice that is an act that is prohibited in Indonesia because it is contrary to moral, religious and cultural values. However, even though the act is prohibited in Indonesia and has been regulated in the law as a preventive effort to provide a solution to the practice of prostitution in Indonesia. The practice of prostitution in Indonesia is still happening and is increasingly rampant in the land of Indonesia and in the legal regulation of prostitution it is still not effective so that the perpetrators of this prosthetic practice still exist and are growing.  As the location of ineffectiveness and some paradoxes in regulating the law against prostitution, there is a legal imbalance between the service user and a prostitute, so it gives me the desire to write this as a form of injustice between a prostitute and a prostitution service user.